Novel fluorescent triazinobenzimidazole derivatives as probes for labelling human A1 and A2B adenosine receptor subtypes. Issue 22 (1st December 2018) - Barresi, Elisabetta; Giacomelli, Chiara; Daniele, Simona; Tonazzini, Ilaria; Robello, Marco; Salerno, Silvia; Piano, Ilaria; Cosimelli, Barbara; Greco, Giovanni; Da Settimo, Federico; Martini, Claudia; Trincavelli, Maria Letizia; et al.
Graphical abstract: Abstract: The expression levels and the subcellular localization of adenosine receptors (ARs) are affected in several pathological conditions as a consequence of changes in adenosine release and metabolism. In this respect, labelled probes able to monitor the AR expression could be a useful tool to investigate different pathological conditions. Herein, novel ligands for ARs, bearing the fluorescent 7-nitrobenzofurazan (NBD) group linked to the N 1 (1, 2 ) or N 10 (3, 4 ) nitrogen of a triazinobenzimidazole scaffold, were synthesized. The compounds were biologically evaluated as fluorescent probes for labelling A1 and A2B AR subtypes in bone marrow-derived mesenchymal stem cells (BM-MSCs) that express both receptor subtypes. The binding affinity of the synthetized compounds towards the different AR subtypes was determined. The probe3 revealed a higher affinity to A1 and A2B ARs, showing interesting spectroscopic properties, and it was selected as the most suitable candidate to label both AR subtypes in undifferentiated MSCs. Fluorescence confocal microscopy showed that compound3 significantly labelled ARs on cell membranes and the fluorescence signal was decreased by the cell pre-incubation with the A1 AR and A2B AR selective agonists, R-PIA and BAY 60-6583, respectively, thus confirming the specificity of the obtained signal. In conclusion, compound3 could represent a useful tool to investigate the expression pattern of both A1 and A2B ARs in different pathological and physiological processes. Furthermore, these results provide an important basis for the design of new and more selective derivatives able to monitor the expression and localization of each different ARs in several tissues and living cells.